Nocardia cyriacigeorgica infection in a patient with pulmonary sequestration: A case report - Lin, Jian (World J Clin Cases, 2021)
BACKGROUND: Nocardia cyriacigeorgica (N. cyriacigeorgica) infection is uncommon in clinical practice. Pulmonary sequestration complicated with N. cyriacigeorgica has not been reported in the literature. Here, we present a case of pulmonary se-questration complicated with N. cyriacigeorgica infection in an immunocom-petent woman. CASE SUMMARY: A 37-year-old woman complaining of a recurrent cough was admitted to our hospital. Pulmonary sequestration in the lower lobe of the left lung was diagnosed by enhanced computed tomography. Bronchoalveolar lavage fluid was then collected, which showed gram positive bacilli with weakly positive modified acid-fast staining. The pathogen was identified as N. cyriacigeorgica after bacterial culture and mass spectrometry analysis. The patient was diagnosed with pulmonary sequestration complicated with N. cyriacigeorgica infection, and her symptoms quickly improved following anti-infective therapy. CONCLUSION: Nocardiosis is considered to be an opportunistic infection. This is the first report of pulmonary sequestration complicated with N. cyriacigeorgica infection in a patient with normal immunity.